2014
DOI: 10.1371/journal.pone.0114966
|View full text |Cite
|
Sign up to set email alerts
|

Antibody and Plasmablast Response to 13-Valent Pneumococcal Conjugate Vaccine in Chronic Lymphocytic Leukemia Patients – Preliminary Report

Abstract: BackgroundChronic lymphocytic leukemia (CLL) leads to significant immune system dysfunction. The predominant clinical presentation in 50% of patients involves recurrent, often severe, infections. Infections are also the most common (60–80%) cause of deaths in CLL patients. The scope of infections varies with the clinical stage of the disease. Treatment-naive patients typically present with respiratory tract infections caused by encapsulated bacteria Streptococcus pneumoniae and Haemophilus influenzae. Since 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
64
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(69 citation statements)
references
References 42 publications
2
64
0
3
Order By: Relevance
“…Pasiarsky and colleagues in a recent work analyze antibody and plasmablast response to 13–valent pneumococcal conjugate vaccine in Chronic Lymphocytic Leukemia Patients 53. They evaluated levels of specific pneumococcal antibodies, the levels of IgG and IgG subclasses and selected peripheral blood lymphocyte subpopulations including the frequency of plasmablasts before and after immunization.…”
Section: Resultsmentioning
confidence: 99%
“…Pasiarsky and colleagues in a recent work analyze antibody and plasmablast response to 13–valent pneumococcal conjugate vaccine in Chronic Lymphocytic Leukemia Patients 53. They evaluated levels of specific pneumococcal antibodies, the levels of IgG and IgG subclasses and selected peripheral blood lymphocyte subpopulations including the frequency of plasmablasts before and after immunization.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, in this population, antibody responses to PSV23 positively correlate with hematologic response to chemotherapy [85]. The conjugated 13-valent pneumococcal vaccination (PCV13) depends more heavily upon T-cell responses, and remains more immunogenic in many immunocompromised cancer populations [86-88]. …”
Section: Introductionmentioning
confidence: 99%
“…41 Unfortunately, modern conjugated vaccine preparations, which recruit T-cell "help" are still not generally capable of fully overcoming suboptimal immune responses. 44 In a recent study, an adequate response to an initial dose of 13-valent pneumococcal conjugate vaccine was found in only 58% of CLL patients compared with all healthy age-matched controls. 44 This study also observed a very poor increment of plasmablasts within peripheral blood at 1 week after vaccination.…”
mentioning
confidence: 96%
“…44 In a recent study, an adequate response to an initial dose of 13-valent pneumococcal conjugate vaccine was found in only 58% of CLL patients compared with all healthy age-matched controls. 44 This study also observed a very poor increment of plasmablasts within peripheral blood at 1 week after vaccination. Overall the clinical observations suggest that both a direct suppression of B-cell function and an impairment of cognate T-cell help contribute to the poor response to vaccines.…”
mentioning
confidence: 96%